State Conservatory of Uzbekistan ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides information about the history and development of the State Conservatory of Uzbekistan, its conditions, educational directions, scientists who worked in the conservatory, the meaning and origin of the word conservatory.